Deskripsi Upaya Guru Dalam Menumbuhkan Minat Baca Siswa Kelas III Di SDN 15 Sungai Raya - Putnawati, Putnawati; Setyowati, Dessy; Hertati, Elvani (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the teacher's efforts in fostering the reading interest of third-grade students at SDN 15 Sungai Raya, focusing on four areas: (1) reading attention, (2) reading fondness, (3) reading time, and (4) the number of reading books. The research method used was a descriptive qualitative method with data collection techniques of interview and observation. The subject of this study was the III-C class teacher, and the object of this study was 25 students of class III-C at SDN 15 Sungai Raya, consisting of 12 male students and 13 female students. The research findings on the teacher's efforts to foster students' reading interest indicate that the third-grade teacher implemented various strategies to enhance students' reading interest, including habitual reading for fifteen minutes before lessons, providing attractive reading materials, giving motivation, and appreciation to actively reading students. Nevertheless, there are still obstacles such as the limited collection of reading books that match students' interests. Overall, the efforts made by the teacher have had a positive impact in forming a reading culture within the classroom environment.